Systematic Review: A Literature Review on Systematic Integrative Intervention Model for Klitih Issue in Yogyakarta - Dody Hartanto; Mufied Fauziah; Ewang Sewoko; Karsih Karsih (Universitas Ahmad Dahlan, 2021)
Klitih constitutes a juvenile delinquency that has reached an alarming level as the case keep occurs every year. This study aims to design the intervention model for handling (preventive-solution) klitih problem in the Special Region of Yogyakarta, Indonesia. This systematic review summarized results of primary study to provide more comprehensive, balanced fact. Data were obtained from articles in research journals about klitih. 297 Articles on klitih published between 2017-2020 were found. Of these articles, eleven articles were selected based on their relevance to the research question of this study. The data were content-analyzed, resulting in three important categories: family, school, and community. The family plays an important role in satisfying basic adolescents needs and internalizing positive values. Meanwhile, the school functions to identify students prone to juvenile delinquency and perform preventive, curative, and preservative plans for these students. Lastly, the community’s role is to provide a positive learning environment for students and sufficient activity to provide adolescents with various opportunities. The results of the study can be used as a reference for school counselors when handling klitih problem.